EUROPEAN SYSTEM OF VOCATIONAL EDUCATION AND TRAINING: TOWARDS A UNIFIED APPROACH (Comparative Professional Pedagogy, 2025)
The European system of vocational education and training (VET), which is characterized by its diversity in different EU member states, faces the problem of unifying programs taking into account the specifics of the socio-economic conditions of each country. Recognition of the vital importance of vocational education and training in addressing industrial challenges and promoting economic growth has led to the consolidation of European education policy towards a common VET strategy.The study provides an overview of the main directions for the development of the European system of vocational education and training, emphasizing the importance of a unified approach to VET.  It is noted that a successful European strategy should take into account a new technological level, regional/national characteristics of human resources in terms of traditional skills and competencies, and, most importantly, natural resources, which are a crucial factor in industrial efficiency and competitiveness.The article presents information on the European VET landscape, revealing the diversity of approaches and the active recognition of dual education programs. It is emphasized that the recognition of vocational education and training as a significant investment and the use of its potential to solve European production problems indicates the urgency of supporting and improving VET systems.The alignment of European education policy with the common VET strategy demonstrates the commitment of policy makers and stakeholders to addressing the current problems and future challenges that will arise in the context of human labor resources. It is found that by implementing a comprehensive VET strategy that prioritizes skills acquisition, social justice, and international recognition, Europe can successfully ensure the transition to a green and digital economy. This strategy aims to promote adaptation, employment, and lifelong learning, while ensuring equal access and support for all people. The article outlines the stages of developing a common, basic set of skills for VET institutions, which provide a structured basis for the implementation of education policy, promoting alignment with sectoral needs and standardization.
Keywords: European Union; EU countries; vocational education and training; development strategies; unified program; qualification framework